An Innovative of Simul Model for Ready-Mix Concretes in The Concept of Third Party Logistics and Supply Chain Management in Malaysia and Thailand - Melan, Mustakim; Sabar, Rohafiz; Anuar, Nur Khairiel; Omotayo, Adebare; O, Alonge (International Journal of Supply Chain Management, 2020)
The research discusses on issues in an order fulfilment for sustainable ready-mix concrete as desired for an eco-friendly choice of integration in the concept of third-party logistics and supply chain management. There are insufficient and inappropriate means in concrete industry which has contributed to un-environmentally friendly especially in Malaysia and Thailand. The supply management and logistics are the factors in designing of product which influence on the environmental, safety and health. It also involves on costs of energy, effectiveness, economic certainty, businesses and other related issues. Through the current practices with relevant factors, the analysis of model is no longer realistic. The sustainable of simulation in logistics model should relate to descriptive approaches. Through the less numbers of movements and reduction on carbon dioxide are significant for the simulation. In some developing countries, the involvements of commercial players and government bodies have their responsibility in controlling, simulating economic and business development. Relation to this fundamental deficiency, this paper utilized SIMUL model in the logistics for sustainable ready mixed concrete, eco-friendly and to meet on the order fulfilments. The result clearly indicates that the eco-friendly SIMUL model can be more sustainable, cost efficient and time effective in fulfilling orders for the operational of ready-mix concrete in future.